2021
DOI: 10.3389/fcell.2021.595911
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes From M2 Macrophage Promote Peritendinous Fibrosis Posterior Tendon Injury via the MiR-15b-5p/FGF-1/7/9 Pathway by Delivery of circRNA-Ep400

Abstract: Achilles tendon rupture prognosis is usually unsatisfactory. After the tendon is injured, it may not function properly because of the fibrotic healing response, which restrains tendon motion. Inflammatory monocytes and tissue-resident macrophages are indispensable regulators in tissue repair, fibrosis, and regeneration. Exosomes from macrophages are crucial factors in tissue microenvironment regulation following tissue injury. This study therefore aimed to clarify the roles of macrophage exosomes in tendon inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…However, the role of DSF on macrophage is unknown. In TI, the functional phenotype change of M1 and M2 exhibits a phagocytic and pro-inflammatory function, which plays an important role in the healing process ( Chamberlain et al, 2021 ; Yu et al, 2021 ). Furthermore, the reduced macrophage-mediated inflammation in the injured tendon through M1-to-M2 transmission significantly inhibits adhesion formation during tendon healing ( Dong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of DSF on macrophage is unknown. In TI, the functional phenotype change of M1 and M2 exhibits a phagocytic and pro-inflammatory function, which plays an important role in the healing process ( Chamberlain et al, 2021 ; Yu et al, 2021 ). Furthermore, the reduced macrophage-mediated inflammation in the injured tendon through M1-to-M2 transmission significantly inhibits adhesion formation during tendon healing ( Dong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…and ultimately promote the expression of fibrosis-related genes. ncRNA in the MAPK Pathway miR-21 [87], miR-127-3p [88], miR-43 [23], miR-32-5p [89], miR-338-3p [90], miR-155 [91], miR-22 [92], miR-503 [78], lncRNA FENDRR [93], and circEP400 [94] can affect the activation of the MAPK signaling pathway and regulate the differentiation of fibroblasts into myofibroblasts. We found that most of these ncRNAs did not directly target molecules in the MAPK pathway but targeted some proteins regulating the MAPK signaling pathway, such as PDCD4, DUSP1, SPRY1, etc.…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%
“…In turn, macrophage-derived exosomes promote fibrosis after tendon injury mainly through the MIR-15b-5p/FGF-1/7/9 pathway in the context of mediating circRNA-Ep400, which not only reveals the mechanism of association between macrophages and stromal cells, but also explores the role of exosomes in the process of tendon adhesion. However, further experiments are still required to verify their effectiveness on scar adhesion [ 38 , 39 ].…”
Section: Illustrations Of Different Sources Of Exosomes In Preclinica...mentioning
confidence: 99%